Transforming History Teaching: Using Adobe Photoshop E-Posters to Teach the Battle of November 10, 1945 - Syahputra, Gunawan; Edwards , Avanelle Joseph (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research focuses on designing an e-poster using adobe photoshop to teach the battle of 10 november 1945 to class 11 social science 2 and 11 social science 3 high school State 1 Jambi City. It aims to assess students' learning interests using e-poster media and identify differences in these interests. Methodology: This research uses a Research and Development (R&D) approach with the ADDIE model. The research subjects were class 11 students. The data collection instruments for this research are open interviews and validation questionnaires as well as student learning interest questionnaires. Data analysis uses parametric statistics for quantitative data and qualitative data using the Miles and Huberman models. Main Findings: The main results of this research show that e-poster media based on adobe photoshop is effective in increasing students' interest in learning. The average interest in learning in the experimental class is higher compared to the control class. The t test confirmed a significant difference with a p-value of 0.011. Validation by material and media experts shows that the e-poster is very good and suitable for use. Small and large group trials received very positive responses from students, indicating the success of this learning media in increasing students' interest and motivation to learn. Novelty/Originality of this study: The novelty of this research is the development and use of adobe photoshop-based e-poster media for history learning, which has proven effective in increasing students' interest in learning.